EFFECT OF CALCIUM HYDROXIDE-PROPOLIS COMBINATION ON THE NUMBER OF FIBROBLAS CELLS AND ANGIOGENESIS IN WISTAR RATS PULP - Nirawati Pribadi; Ira Widjiastuti; Agata Nadia (Conservative Dentistry Journal, 2020)
Background: The vitality of the pulp must be protected because the pulp contains fibers, cells, and various structures. Pulp vitality can be maintained by pulp capping to stimulate the formation of reparative dentin. The material commonly used for pulp capping is calcium hydroxide. Calcium hydroxide has the disadvantage of causing inflammation and necrosis of the pulp surface. To compensate that, propolis is added because it has the ability as an anti-inflammatory. Purpose: To analyze the increase in the number of fibroblast cells and angiogenesis in the pulp after the application of  combination of Calcium hydroxide-propolis compared to the application of Calcium hydroxide.. Methods: This study used 30 samples of wistar rats which were preparated until perforation and then divided into 3 groups. The first group continued with filling with cention, the second group continued with application of calcium hydroxide and filled with cention, and the third group continued with the application of combination of calcium hydroxide and propolis and then being filledwith cention. fibroblast cells and angiogenesis is calculated histopathologically by using compound light microscopeon the 7th day with 400x magnification.Results:Based on the results of the study found a significant difference between the calcium hydroxide group and the calcium hydroxide-propolis group. Increased numbers of fibroblasts and angiogenesis indicate a faster inflammatory process that affects the acceleration of wound healingConclusion: More number of fibroblasts and angiognesis cells found in the pulp after the application of a combination of Calcium hydroxide-propolis compared to the application of Calcium hydroxide